A brief review on factors affecting flow and pool boiling. (September 2019) - Dadhich, Manish; Prajapati, Om Shankar
Abstract: Boiling is a phenomenon in which heat transfer causes liquid evaporation. Boiling phenomenon; when the liquid is imposed by a forced flow is termed as flow boiling and in pool boiling heating surface is submerged in stagnant liquid. Suspended nanoparticles of small size and concentration dispersed in liquids like oil, water etc. are called nanofluid and are heat transfer carrier due to their thermo physical properties. CHF and HTC in boiling are affected by enhanced surface, nanoparticles size, nanofluids concentration and its development, thermo physical properties, like density, specific heat, thermal conductivity and viscosity of nanofluids. Goal of this paper is to review critical heat flux and heat transfer in nanofluid in flow and pool boiling and to understand in better way. Compilation of equations for estimation of thermal conductivity, viscosity etc. from past research has been briefly shown. These equations have adaptability for determination of nanofluid properties for various working parameters. Different experimental procedures of pool and flow boiling, multiphase computational schemes, computational modeling of bubble nucleation, growth and departure has been discussed. One and two stage techniques for nanofluid formulation and approvals of numerical simulation against experimental data have been represented. Current advances in flow and pool boiling of nanofluid to determine HT and CHF has been discussed. CHF enhancement process by surface modifications in pool and flow boiling is accomplished. Finally, for CHF enhancement in flow and pool boiling concluding remarks are given followed by future studies. Highlights: This review explores the thermal transport properties of nanofluids. Examination on experimental and numerical investigations on boiling of nanofluids. Review of different methods of nanofluids preparation. Discussion on effect on Heat Transfer Coefficient and Critical Heat Flux during boiling. Overviews on effect of surface change on pool and flow boiling.